Alborz and its Teachers - Katouzian, H (2011)
The success story of Alborz High School was due to a number of factors. The legacy of Dr. Jordan and other of its American founders had set unusually high standards of teaching, behavior, discipline and conduct. Dr. Mojathedi managed to maintain those standards through dedication and hard work, even though there was occasional friction between him and students and teachers. Almost all the students, some of them from the upper echelons of society, came from educated and cultured homes, had performed well at their primary schools, were well-motivated, loved their school, ran various cultural programs by themselves, and included notable writers, poets, artist and athletes. Teachers generally maintained discipline, good humor and high standards, and included stars of altogether different varieties such as Zeinolabedin Motamen, Dr. Mahmud Behzad and Mostafa Sarkhosh. © 2011 The International Society for Iranian Studies.